2012
DOI: 10.1007/s10661-012-2578-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing genetic structure, diversity of bacterial aerosol from aeration system in an oxidation ditch wastewater treatment plant by culture methods and bio-molecular tools

Abstract: Airborne bacteria emissions from oxidation ditch with rotating aeration brushes were investigated in a municipal wastewater treatment plant in Beijing, China. Microbial samples were collected at different distances from the rotating brushes, different heights above the water surface, and different operation state over a 3-month period (April, May, and June) in order to estimate the seasonal variation and site-related distribution characteristics of the microorganisms present. The concentration of bacterial aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 40 publications
(37 reference statements)
1
13
0
Order By: Relevance
“…While other studies have reported concentrations of airborne bacteria around WWTPs, 24,27,30,32 fewer have focused on airborne viruses. 34,40 Our results show that viable virus can be aerosolized from an aeration basin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While other studies have reported concentrations of airborne bacteria around WWTPs, 24,27,30,32 fewer have focused on airborne viruses. 34,40 Our results show that viable virus can be aerosolized from an aeration basin.…”
Section: Discussionmentioning
confidence: 99%
“…These aerosolized microorganisms can maintain their viability and spread in ambient air. 28,29,31,32 The potential for EBOV to spread via this route is not known. Previous studies have focused mainly on bacteria rather than viruses, and they have not measured the full range of aerosol sizes produced by flush toilets.…”
Section: Potential For Aerosol Transmission Via Wastewatermentioning
confidence: 99%
See 1 more Smart Citation
“…Airborne bacteria and fungi generated from an Orbal oxidation ditch in a wastewater treatment plant in Beijing were investigated, and 3952 ± 730 CFU/ m 3 of airborne bacteria were detected from the point near the rotating brushes in June (Li et al 2013). Approximately 8 9 10 4 m 3 /day water was treated in the WWTP.…”
Section: Diversity and Richness Estimation Of Clone Librariesmentioning
confidence: 99%
“…The concentration of airborne Mean concentration and standard deviation in S1(CFU/m 3 air) S1 S2 Fig. 4 Site-related emission of airborne bacteria and fungi in June bacteria was investigated in an Orbal oxidation ditch in a Beijing municipal WWTP, and outcome demonstrated that the airborne bacteria decreased dramatically with increasing distance from the rotating brushes (Li et al 2013). The concentrations of airborne bacteria and fungi that emerged in the air increased with increasing proximity to the bioaerosol source.…”
Section: Seasonal Variationmentioning
confidence: 99%